Coronary risk factor modification after coronary artery bypass surgery - Lim, Meng Chee, 1973- (2002)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2003. Medicine Bibliography: leaves 95-101 This is a retrospective cohort study that examined whether major coronary risk factors change when compared preoperatively and 3 years postoperatively after coronary artery bypass surgery. Preoperative coronary risk factor data were obtained from a retrospective chart review. Three years postoperative risk factor data were obtained by hospital attendance with blood sampling, blood pressure measurements, weight and height measurements, and answering standard questionnaires. Results revealed a significant decrease in total cholesterol and LDL, a significant increase in blood pressure and body mass index, and a clinically significant change in smoking habits 3 years post surgery. Slightly more than half of the subjects reported an increase in exercise levels even though only one fifth of them attended cardiac rehabilitation program post surgery. Most subjects reported strong social support in helping them to modify their coronary risk factors. Implications for the current strategies in the secondary prevention of coronary artery disease were examined.